2012
DOI: 10.1021/ja304618v
|View full text |Cite
|
Sign up to set email alerts
|

Kinetically Blocked Stable Heptazethrene and Octazethrene: Closed-Shell or Open-Shell in the Ground State?

Abstract: Polycyclic aromatic hydrocarbons with an open-shell singlet biradical ground state are of fundamental interest and have potential applications in materials science. However, the inherent high reactivity makes their synthesis and characterization very challenging. In this work, a convenient synthetic route was developed to synthesize two kinetically blocked heptazethrene (HZ-TIPS) and octazethrene (OZ-TIPS) compounds with good stability. Their ground-state electronic structures were systematically investigated … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

16
186
1

Year Published

2013
2013
2017
2017

Publication Types

Select...
6
3

Relationship

1
8

Authors

Journals

citations
Cited by 270 publications
(207 citation statements)
references
References 72 publications
16
186
1
Order By: Relevance
“…87 This derivative 42 showed biradicaloid behavior; broad 1 H NMR signals in the aromatic region, small ¦E ST (16.2 kJ mol ¹1 ), and an ESR signal in the solid state. The amount of singlet biradical character (y) was estimated to be 43% by a broken symmetry UCAM-B3LYP calculation.…”
Section: Zethrenesmentioning
confidence: 95%
“…87 This derivative 42 showed biradicaloid behavior; broad 1 H NMR signals in the aromatic region, small ¦E ST (16.2 kJ mol ¹1 ), and an ESR signal in the solid state. The amount of singlet biradical character (y) was estimated to be 43% by a broken symmetry UCAM-B3LYP calculation.…”
Section: Zethrenesmentioning
confidence: 95%
“…20 Bulky triisopropylsilyl (TIPS) ethynyl groups are attached to the most reactive sites by nucleophilic addition of the corresponding quinones followed by reduction with SnCl 2 . The kinetical blocking by TIPS group and the extended spin delocalization to the ethynyl unit make the compounds 36 and 38 as very stable materials.…”
Section: Extended Zethrenesmentioning
confidence: 99%
“…Zethrenes with six, seven and eight rings (136, 137, and 138) have been synthesized and studied for their dynamic open-shell to close-shell properties (Chart 9) [156,157] (140) [156]. Compound 139 was found to be a closed-shell Kekule hydrocarbon as it exhibited sharp 1 H-NMR signals at room temperature due to a large singlet-triplet energy gap and only a minute quantity of triplet species.…”
Section: Zethrenesmentioning
confidence: 99%
“…Zethrenes with six, seven and eight rings (136, 137, and 138) have been synthesized and studied for their dynamic open-shell to close-shell properties (Chart 9) [156,157]. Recently, Wu et al reported a series of derivatives of zethrenes: zethrenebis(dicarboximide) (139), and heptazethrenebis(dicarboximide) (140) [156].…”
Section: Zethrenesmentioning
confidence: 99%